Literature as Heritage: from Nation Building to Nation Branding - Santos Unamuno, Enrique (Tropelías: Review of Literary Theory and Comparative Literature, 2018)
Starting from the concept of heritage as a legacy able to create economic value and well aware of the difficulties involved in defining precisely what is literary heritage, this paper tries to deal with two successive paradigms regarding the creation of sociocultural cohesion and national identity on the basis of the idea of literature as heritage asset. If modern soft processes of nation building have been well tackled by Polysystem Theory, the nation branding approach (selling and buying national identity as a product depending on the corporate image of a brand-State) has come up in the context of globalised postmodernity as a new nationalizing strategy giving great weight to cultural and literary heritage as symbolic and economic assets. This kind of «venal nationalism» quite underpins today’s legacy work tied to the market of identities. Somehow, the struggle of polysystem theories when trying to differentiate institution and market has vanished due to the fusion of both sociocultural factors. As a consequence, this context requires new ways of thinking about literary practices and cultural systems.
Keywords: Cultural and literary heritage; Polysystem Theory; Nation Building; Nation Branding; Competitive Identity; Market of identities; Venal nationalism